Periodic Structural Defects in Graphene Sheets Engineered via Electron Irradiation - Nicola Melchioni; Filippo Fabbri; Alessandro Tredicucci; Federica Bianco (Micromachines, 2022)
Artificially-induced defects in the lattice of graphene are a powerful tool for engineering the properties of the crystal, especially if organized in highly-ordered structures such as periodic arrays. A method to deterministically induce defects in graphene is to irradiate the crystal with low-energy (<20 keV) electrons delivered by a scanning electron microscope. However, the nanometric precision granted by the focused beam can be hindered by the pattern irradiation itself due to the small lateral separation among the elements, which can prevent the generation of sharp features. An accurate analysis of the achievable resolution is thus essential for practical applications. To this end, we investigated patterns generated by low-energy electron irradiation combining atomic force microscopy and micro-Raman spectroscopy measurements. We proved that it is possible to create well-defined periodic patterns with precision of a few tens of nanometers. We found that the defected lines are influenced by electrons back-scattered by the substrate, which limit the achievable resolution. We provided a model that takes into account such substrate effects. The findings of our study allow the design and easily accessible fabrication of graphene devices featuring complex defect engineering, with a remarkable impact on technologies exploiting the increased surface reactivity.